Sources and trends of trace elements and polycyclic aromatic hydrocarbons in a shallow lake in the Mediterranean area from sediment archives of the Anthropocene - Paola Gravina; Bartolomeo Sebastiani; Federica Bruschi; Chiara Petroselli; Beatrice Moroni; Roberta Selvaggi; Enzo Goretti; Matteo Pallottini; Alessandro Ludovisi; David Cappelletti (Environmental Science and Pollution Research, 2022)
In this study, the anthropogenic contamination in Trasimeno lake (Central Italy) was investigated using three sediment cores spanning over the last 150 years (Anthropocene) to identify the primary sources of pollution and quantify the level of contaminant enrichment in the basin. First, based on the relative cumulative frequency and linear regression methods, we obtained a geochemical baseline for the lake using the deeper parts of the sediment cores. The geochemical baseline allowed us to determine the values of trace elements enrichment factors. On this knowledge, as a second result, we were able to reconstruct the natural sources and the anthropogenic impact on the lake with a biennial resolution. This goal has been obtained by combining different inorganic and organic chemical proxies such as trace elements, polycyclic aromatic hydrocarbons, and lead isotope ratios and exploiting both principal component and factor analysis to associate chemical proxies to human-driven contamination processes. Five different groups of elements have been identified, one of which is of natural origin and four of anthropogenic origin. In particular, it was possible to identify the times and impacts of the industrial activities during the Second World War, which dispersed heavy metals in sediments. Moreover, we found evidence of the recent human activities that have characterized the surroundings of the basin, such as Pb inputs related to the use of gasoline and the enrichment of certain elements generally used in agricultural activities (such as P, Cu, and Mn) due to the development of this sector in the last 40 years.

Paint it green: A neuroscientific approach to hotel sustainability and ecological tourism - Giulia Fronda; Federico Cassioli; Roberta Sebastiani; Annalisa Beatrice Galeone; Michela Balconi (Environment, Development and Sustainability, 2021)